HIGH-ACCURACY MEASUREMENTS WITH A GRAVITATIONAL VARIOMETER - Gridnev D.G.; Naumenko-Bondarenko I.I.; Kaganovskiy I.P.; Smirnov Y.I. (My University, 1988)
Data on the absolute magnitude of the second derivatives of the gravitational potential can be obtained only with gravity variometers. But a measurement accuracy of a fraction of an eotvos can be attained only in the dynamic mode and with recording systems that use new components. The authors developed two such systems for the E-60 variometer: a photoelectric system and a system making use of a charge-coupled device (CCD) video signal shaper. The article discusses the design and application of these systems.